STRATEGI PENGEMBANGAN EKOWISATA DI HUTAN BAMBU KABUPATEN LUMAJANG - Maulida Lujeng Sri Rahayu; Wahyu Hidayat Riyanto; Yunan Syaifullah (Program Studi Ekonomi Pembangunan, 2020)
This research aims to study the Strategy for Developing Bamboo Forest Ecotourism in Lumajang Regency. This type of research is a type of qualitative descriptive research. The source of the data used in this study is primary data. Primary data is the main research data obtained by researchers at the time researchers in the field. Primary data in this study consisted of interviews. This research was conducted in the Bamboo Forest tourism area in Lumajang Regency. Analysis of the data used is the analysis of SWOT (Strengths, Weaknesses, Opportunity, Threats). The results showed that the Bamboo Forest Ecotourism in Lumajang District produced several strategies for developing the Bamboo Forest Ecotourism that included improving management systems to encourage community empowerment, collaborate with parties or travel agents, increase potential, improve infrastructure, and carry out promotions. Bamboo Forest has adequate facilities to carry out various activities. Ecotourism management is expected to add supporting infrastructure of Bamboo Forest ecotourism and maintain the ecotourism sustainability.